An Onward Progressive March Of The Kingdom Of Saudi Arabia (Ksa): Some Pointers - Richa Thapliyal; Dr. Mandakini Sharma (Elementary Education Online, 2023)
With the ongoing spate of trade wars and the consequent economic uncertainty looming large in the face of global economies, several macro-environmental challenges are gripping the attention of the economies-developed and developing, both. The Kingdom of Saudi Arabia (KSA) is pushing forth a progressive agenda to tackle the challenges posed by the hydrocarbon sector which has hitherto remained the chief plank of its economic growth. In this vein, the country has explored avenues into non-hydrocarbon spaces in order to steer the country forward. IMF has been appreciative of the efforts of the country in terms of the reforms undertaken so far (The National, 2018)i. At the same time, the IMF has issued an advisory to the country not to increase government spending as the oil prices rise (Reuters, 2018)ii. As such, the country has undertaken reforms like the launch of the Value Added Tax (VAT) and the opening up of the capital markets to foreign investors. The proposed IPO of SAUDI ARAMCO in 2019 is expected to add to the revenues. Very recently, the Saudi Capital Markets Authority (SCMA) has been included in the MSCI’s Emerging Markets Index and this would further facilitate market stability, increase institutional investments and enhance market attractiveness and liquidityiii. With this background, it is as well opportune to appreciate the onward progressive march of the Kingdom of Saudi Arabia (KSA) in terms of economic diversification initiatives. Specifically, the country is seeking to push forth its economy with an emphasis upon investments, education, entrepreneurship, tourism, and the like.